Effect of Alkyl Phenol from Cashew Nutshell Liquid and Sisal Fiber Reinforcement on Dry Sliding Wear Behavior of Epoxy Resin. Issue 5 (3rd September 2017) - Panda, Rajesh; Tjong, Jimmi; Nayak, Sanjay K.; Sain, Mohini
ABSTRACT: A phenalkamine made from the reaction of alkyl phenol from cashew nut shell liquid (CNSL) and alkaylamine was added at three different weight percentages (30%, 40%, and 50%) as a hardener for curing the epoxy polymer. The effect of phenalkamine concentrtation on mechanical and dry sliding wear resistance properties were compared to synthetic aliphatic amine (TETA) cured epoxy network. It was obsererved that incorporation of phenalkamine improves the dry sliding wear resistance property of the epoxy network along with the impact strength and elongation properties. Epoxy composites incorporating sisal fiber placed unidirectionally (either parallel, anti-parallel, or perpendicular to the sliding direction) were prepared in a vacuum infusion process using phenalkamine as a crosslinking agent. It was observered that wear resistance of longitudinally oriented fibers composite was found to be higher owing to the area of fibers exposed to sliding asperities being smaller. With the goal to understand the brittleness behavior of epoxy networks, fractured surfaces of the epoxy networks were analyzed using optical microscope. A correlation was found between the mechanical and wear resistance properties of the epoxy networks.